2019
DOI: 10.31663/tqujes.10.1.360(2019)
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation the performance of micro channel heat sink with different cooling mediums

Abstract: This study aims to study the effect of different cooling fluids (pure fluids, Nanofluids and microencapsulated phase change materials suspensions) and the cooling performance of rectangular micro-channel heat sink. Three types of Nanofluids (Al2O3-water, Cu-water,Tio2-water), three types of microencapsulated phase change materials suspensions(MEPCM) are(RT44-water, paraffin wax water, n-octed-water ) and three pure fluids ) Water, Oil ,Ethylene Glycol ) were used with constant heat flux(100 W /cm 2 ) applied o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Mushtaq et al. 40 used three different types of pure fluids, nanofluids and microencapsulated phase change material suspensions respectively to investigate the performance of the microchannel with fins or without fins of various shapes numerically. Yadav et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mushtaq et al. 40 used three different types of pure fluids, nanofluids and microencapsulated phase change material suspensions respectively to investigate the performance of the microchannel with fins or without fins of various shapes numerically. Yadav et al.…”
Section: Introductionmentioning
confidence: 99%
“…Turker et al 39 analyzed the performance of single miniature sized fin of various shapes with the same chord diameter on low Reynolds number ranging from 20 to 120. Mushtaq et al 40 used three different types of pure fluids, nanofluids and microencapsulated phase change material suspensions respectively to investigate the performance of the microchannel with fins or without fins of various shapes numerically. Yadav et al 41 examined the three distinct setups of fins in microchannel and concluded that the fins at upstream region are more effective than at the downstream region and complete finned arrangement while Owais et al 42 attempted to explore the outcome of variation of height of pin fins by considering the microchannel with increasing and decreasing height of pin fin and compared it with plain rectangular microchannel.…”
Section: Introductionmentioning
confidence: 99%